The model of evaluating the criteria, describing the quality of organization and technology of travel by international train - Sivilevičius, Henrikas; Maskeliūnaitė, Lijana; Petkevičienė, Birutė; Petkevičius, Kazys (Transport, 2012)
The significance of the criteria describing various aspects of travel by train, e.g. passenger transportation comfort, safety, travel time, price of a journey, etc., differs considerably. The quality of particular trains, track sections and staff performance can be successfully evaluated by a single number, using the comprehensive quality index (CQI). The paper offers an additive model to calculate the normalized weight coefficients of particular criteria for CQI calculation. A multi-criteria mathematical model, which may be used for evaluating the significance of the criteria describing organization and technology of travel by train for determining its quality, is also presented. Based on the nineteen adopted criteria (the criteria of group B), reflecting the organization and technology of travel by train, the quantitative estimate KB is obtained. Case studies of calculating the comprehensive quality index KB , describing the organization and technology of travel by the train ‘Vilnius–Moscow’, which show the real quality of these processes, are presented. Finally, the conclusions based on the research results are provided. First Published Online: 19 Sep 2012